Maple Syrup Urine Disease: Incidence and Related Factors in Infants 2008-2015, Tehran, Iran: - Shahverdi, Ehsan; Najafian, Bita; Konjedi, Mohammad Amin; Tohidi, Mohammad (Galen Medical Journal, 2015)
Background: Maple syrup urine disease is an inherited autosomal recessive disorder. Infants with MSUD appear normal at birth. In Iran, no data concerning the incidence of MSUD has ever been reported. The aims of this study were (a) to estimate the incidence of MSUD in Iran (b) to establish a preliminary comparative analysis of clinical presentation and diagnosis. Materials and Methods: This retrospective analytical study was conducted between 20 March 2008 and 20 February 2015. We evaluated babies born in Najmiyyeh Hospital and referring to Niloo, Masoud and Saeid laboratories in Tehran, Iran. Blood leucine level was measured. Normal leucine levels in blood samples from healthy infants were less than 4.27 mg/dl. In patients whose blood leucine levels were higher, the experiment was repeated once again. If the result was positive again for the final confirmation of the disease in infants, quantitative measurement of amino acids such as leucine, isoleucine and valine was performed by HPLC (high-performance liquid chromatography). The prevalence of MSUD was determined in newborns. Results: Of 200,000 cases, 11 had MSUD. The prevalence was 1:18,180. The mean age of symptom onset was 6Â±2.8 days. Special diets for MSUD, diet and liver transplantation, diet and blood transfusion and peritoneal dialysis were performed on 9, 1, 1, 1, respectively. Conclusion: We should consider the diagnosis of MSUD in infants with poor feeding, lethargy, smell of burnt sugar in the urine and nneurological involvement.[GMJ.2015;4(4):164-68]